The Phenomenon of Cyber Crimes Which Impact Children as Victims in Indonesia - Hardianto Djanggih (Universitas Airlangga, 2018)
The development of internet nowadays does not only give a positive impact but also gives a negative impact in the form of crime that targets everyone, including children. Cyber crime which impact children as a victim should be handled seriously, this considering the fact that children need to get optimal protection to ensure their growth as the hope of nation. This study aims to determine and analyze the impact on cyber crime that impact children as its victim. This research uses juridical-sociological research method which is analyzed descriptively. The results show that the development of cyber crime that afflicts children as victims every year increases with various forms of development and crime mode. However, the legal protection aimed to reduce such crime is still very weak due to weak legislation, law enforcement performance and cyber security in Indonesia. The research is intended to provide recommendation for the government, law enforcers and the public, so that cyber crime that impact children as victims could be reduced and ensure protection for children.